2017
DOI: 10.1159/000476077
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Remote Organs Effect in Acute Kidney Injury Outcome

Abstract: Acute kidney injury (AKI) has been associated with both short- and long-term outcomes. To date, there is still a debate whether the increase risk of morbidity and mortality is directly due to AKI occurrence. There is, however, a potential causal impact of AKI on outcome, but evidence of this association is yet lacking. The hypothesis of remote organ damage and dysfunction (heart, lung, liver, brain, etc.) has emerged over the last decade and may explain the reason for the potential negative impact of AKI on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…[56][57][58][59][60] These observational studies are supported by experimental studies of AKI that provide plausible biological mechanisms for clinically relevant outcomes. [61][62][63][64] In a population that has developed CIN, there is a debate of whether this is associated with a clinically relevant longer-term adverse outcome. Several studies have demonstrated increased in-hospital and longterm mortality, CKD progression, and kidney failure in patients who developed AKI following contrast angiography, compared with those without AKI following coronary angiography.…”
Section: Cect Studies Of Cin With Nonrandomized Control Groupsmentioning
confidence: 99%
“…[56][57][58][59][60] These observational studies are supported by experimental studies of AKI that provide plausible biological mechanisms for clinically relevant outcomes. [61][62][63][64] In a population that has developed CIN, there is a debate of whether this is associated with a clinically relevant longer-term adverse outcome. Several studies have demonstrated increased in-hospital and longterm mortality, CKD progression, and kidney failure in patients who developed AKI following contrast angiography, compared with those without AKI following coronary angiography.…”
Section: Cect Studies Of Cin With Nonrandomized Control Groupsmentioning
confidence: 99%
“…The presence of a multi-scale network of transporters, together with possible compensatory up-regulation between transporters at the renal level [130], could have repercussions in normal physiology and pathophysiology of the transplanted organ and of the whole organism [61]. In this sense, a frequent consequence of reperfusion after localized tissue ischemia is injury to other organ systems, so-called distant or remote organ injury (ROI) [131][132][133], including hepatic changes after renal IR injury [134,135].…”
Section: Alteration Of the Graft Itselfmentioning
confidence: 99%
“…The hypothesis of distant organ injury (lung, heart, brain, liver, etc.) has emerged over the last decade and may demonstrate the reason for the potential negative influence of AKI on outcome [53][54][55] . High mortality rate during AKI is largely due to this multiple organ dysfunction.…”
Section: Remote Organ Injury Following Renal I/r Injurymentioning
confidence: 99%